2011
DOI: 10.1002/jsfa.4426
|View full text |Cite
|
Sign up to set email alerts
|

Dehulled-micronised lupin (Lupinus albus L. cv. Multitalia) as the main protein source for broilers: influence on growth performance, carcass traits and meat fatty acid composition

Abstract: These results suggest that replacing soybean meal with dehulled-micronised lupin meal in diet for broiler chickens can produce meat with favourable lipid profile and quality, with no adverse effects on productive parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 40 publications
3
36
3
1
Order By: Relevance
“…In this experiment, the inclusion of lupine seeds in turkey diets caused a linear increase in both n-6 and n-3 PUFA concentrations, without affecting the n-6/n-3 PUFA ratio, and significantly decreased the atherogenic and thrombogenic indices in meat lipids (P < 0.001). Our findings are in agreement with previous studies conducted by Laudadio and Tufarelli (2011) who examined the effect of lupine-based diets on meat quality in broiler chickens.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this experiment, the inclusion of lupine seeds in turkey diets caused a linear increase in both n-6 and n-3 PUFA concentrations, without affecting the n-6/n-3 PUFA ratio, and significantly decreased the atherogenic and thrombogenic indices in meat lipids (P < 0.001). Our findings are in agreement with previous studies conducted by Laudadio and Tufarelli (2011) who examined the effect of lupine-based diets on meat quality in broiler chickens.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in the concentrations of unsaturated fatty acids in meat from turkeys fed lupinebased diets, noted in our study, is consistent with the results reported by Laudadio and Tufarelli (2011) for broilers. Lupine species differ considerably with regard to lipid fraction composition (Chiofalo et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we evaluated the effects of lupin diets in replacing soybean meal on egg production and egg quality in laying hens. It is well documented that lupin diets, as an alternative to soybean meal, have positive effects on performance, carcass value, and meat quality in broilers (Suchy et al 2010;Laudadio and Tufarelli 2011b). Diets with different concentrations of lupin seeds influenced the average daily feed intake in the present study.…”
Section: Discussionmentioning
confidence: 49%
“…In particular, milling, pelleting and micronizing processes increase the digestibility in poultry of protein and starch and apparent metabolizable energy values of forages [28,29]. In this regard, some antinutritional factors such as tannins are mainly concentrated in the seed coat, so that hulling is a simple method to remove them [30,31].…”
Section: Introductionmentioning
confidence: 99%